Bargaining power and quantity discounts to retailers: Evidence from India's pharmaceutical industry - Gianluca Antonecchia; Ajay Bhaskarabhatla; Enrico Pennings (Tinbergen Institute, 2024)
This paper develops a novel theory linking quantity discounts to bargaining power in scenarios where retailers, organized as a trade association, negotiate uniform wholesale prices with suppliers. Our theory predicts that suppliers offer greater quantity discounts in regional markets where they possess relatively less bargaining power, as a counterbalance to the higher national wholesale prices negotiated by the retailer trade association. We test these predictions using detailed product-level data from the Indian pharmaceutical industry, where significant geographic variations in quantity discounts are observed. Our findings provide empirical support for the proposed theory.
Keywords: L11; L42; D22; 330; quantity discounts; bargaining power; pharmaceuticals; India